EVALUASI RISIKO BANJIR SUBDAS BENGAWAN SOLO HULU TAHUN 2007 PADA DAERAH PERTANIAN DI KABUPATEN SUKOHARJO, KLATEN, DAN KOTA SURAKARTA, JAWA TENGAH DENGAN TEKNIK PENGINDERAAN JAUH - , Andi Renata Ade Yudono, Dr. Sunarto, M.S. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Frequent flooding Solo River around the river is not just due to the addition of the discharge, but there are also other factors that led to the floods, including rainfall, slope, land use, land form and soil moisture. The location of this research is in two regency and one city, there are Sukoharjo regency, Klaten regency, and Surakarta city. All of those locations are location that is food centre for surrounding area. Over the last 10 years in those areas, there were a flood that made an amount of loss around Rp 30.000.000.000,00. The purpose of this study was (1) making a flood prone zone, (2) inventories of areas located in flood-prone zones, (3) calculating the loss when exposed to natural disasters flooding, and (4) evaluating the level of flood risk. , there are The method used in the implementation phase of this research is the method of observation, interviews, and remote sensing, while the finalizing (analysis) using scoring and weighting. In study 2 (two) result types of interviews, the flood vulnerability maps that have occurred in the area of research and the standard value (price) which will be used to determine the loss. For remote sensing techniques, this technique use IKONOS imagery and LANDSAT imagery. IKONOS imagery is used to make land use mapping and LANDSAT imagery is used to determine the shape of the land and soil moisture. To make a soil moisture mapping, this research use Teaselled Cap (TC) method from LANDSAT imagery. the In the area of research, it was found that there are 2 (two) types of zones (map) flood vulnerability, including tentative flood vulnerability (medium, high, and very high) and the final flood vulnerability (low, medium, high, and very high). Based on data from overlying the final flood vulnerability and the productivity value of land, It got level of flood risk. In the study area, there are three levels of risk for flooding, namely the level of low, medium, and high. At the level of risk being. At moderate risk level, largest districts are at that level is the Grogol District, Sukoharjo Regency, with an area of +1,710,129.37 m 2 . In high level of risk, the biggest district is the District Sukoharjo District, Sukoharjo Regency, with an area of +30,232,470.4 m 2 . The highest losses in areas with a high risk level is field in Sukoharjo District, Sukoharjo Regency, around Rp 82,452,190,000.00. The highest Losses in moderate-risk areas are garden on the type of land use, which is located in Grogol District, Sukoharjo Regency around Rp 3,420,260,000.00. Those losses are obtained by Sukoharjo caused by several factors, such as topography in the form of terrain